Molecular Phylogeny of Sporothrix schenckii - Marimon, Rita (American Society for Microbiology, 2006)
The pathogenic dimorphic fungus Sporothrix schenckii is the agent responsible for sporotrichosis, an important fungal infection with a worldwide distribution. Little is known about the population structure of S. schenckii, although recent molecular and phenotypic data seem to demonstrate that different genetic lineages exist within this species. The aim of this study was to determine, by sequence analysis of three protein coding loci (chitin synthase, β-tubulin, and calmodulin), whether this variability is due to species divergence or intraspecific diversity in S. schenckii. We included in the analysis 60 isolates (59 of clinical and 1 of environmental origin) of this species from a wide geographical range. DNA sequence data from the three nuclear regions were used in a phylogenetic analysis. The combined analysis of the three loci revealed the presence of three major clades, one grouping all of the European isolates, another with only Brazilian isolates, and the third with isolates from other South American countries and Africa. A total of 14 100% bootstrap-supported nodes were shown, 6 of them representing putative phylogenetic species. Our data also demonstrated that most of these species prevail in different geographical regions.